MENGENALKAN NARASI BUDAYA DALAM MOTIF BATIK MELALUI PELATIHAN MEMBATIK BAGI MASYARAKAT JEPANG DI KJRI OSAKA - Hana Farida; Intan Rawit Sapanti; Resneri Daulay (ASOSIASI IDEBAHASA KEPRI, 2026)
Batik is one of Indonesia’s cultural heritages that embodies not only artistic value but also philosophical meanings, symbols, and stories reflecting the beliefs and traditions of Indonesian society. Similar to traditional Japanese motifs, which often carry cultural meanings and represent values, wishes, and identities, Indonesian batik motifs are also rich in symbolic significance and cultural narratives. Understanding batik, therefore, involves appreciating both its visual beauty and the meanings embedded within its patterns. This community engagement program was conducted at the Consulate General of the Republic of Indonesia (KJRI) in Osaka and involved learners of Indonesian as a Foreign Language (BIPA) from Japan. The program combined an introduction to the meanings and stories behind selected batik motifs with hands-on batik-making practice. Through this activity, participants gained basic batik-making skills while developing a deeper understanding of Indonesian culture and values. The program demonstrated that batik training can serve as an effective medium for cultural exchange and for enhancing cross-cultural understanding between Indonesia and Japan.